Asia on tour [electronic resource] : exploring the rise of Asian tourism - Chang, T. C.; Teo, Peggy; Winter,Tim , 1971- (New York : Routledge, 2009)
Examining domestic and intra-regional tourism, the book reveals how improvements in infrastructures, ever increasing disposable incomes, liberalized economies, the inter-connectivities of globalization and the lowering of borders, both physical and political, are now enabling millions of Asians to travel as tourists.
Description based on print version record
Includes bibliographical references and index
Keywords: Tourism -- Asia